PENGARUH ISLAMIC LEADERSHIP DAN MOTIVASI KERJA TERHADAP KOMITMEN ORGANISASIONAL: KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Fida Maulidiyah; Tavenna Rosmaya Dewi; Siti Mahmudah (POLITEKNIK LP3I JAKARTA, 2024)
The objective of this research is to explain the affects of Islamic leadership and work motivation on job satisfaction and organizational commitment of employees at PT Usaha Utama Bersaudara (PT UUB). Data was collected using a survey method involving all employees (86 individuals) through a questionnaire with 68 Likert scale statements and observations. The data was analyzed using SPSS 24 and the Sobel Test. The results of the study demonstrate that Islamic leadership and work motivation have a significant impact on job satisfaction, but not on organizational commitment. Job satisfaction significantly affects on organizational commitment and fully mediates and strengthen the relationship between Islamic leadership and work motivation on organizational commitment. Therefore, the company should strengthen Islamic leadership through training that emphasizes Islamic values, enhance motivation with effective strategies and incentives, and improve job satisfaction by enhancing the work environment, recognition, and employee welfare. By doing so, PT Usaha Utama Bersaudara can increase job satisfaction, which positively impacts and strengthens employees' commitment to the organization.